Effect of aeration pattern and gas distribution during scale-up of bubble column reactor for aerobic granulation. Issue 5 (October 2018) - Pishgar, R.; Kanda, A.; Gress, G.R.; Gong, H.; Dominic, J.A.; Tay, J.H.
Graphical abstract: Highlights: Aeration pattern is of prior importance compared to aeration intensity during granulation. Gas distributor characteristics greatly influence on prevailing aeration pattern. Gas holdup is an easy-to-measure controlling parameter for scale-up of granular reactors. Abstract: This study investigates the influence of aeration pattern and gas bubble distribution on aerobic granulation in pilot bubble columns and advances the understanding on crucial factors to be considered during scale-up. Experiments were conducted in a pilot scale bubble column of 22-L capacity. A laboratory-scale bubble column of 5-L capacity, which could achieve granulation in a short time, was used as the control reactor. The pilot reactor was operated with optimal operational conditions evaluated for the control reactor, but the granulation was initially inhibited; improper aeration pattern was found as the most significant factor in precluding granulation. Aerobic granulation in the pilot-scale reactor was achieved upon modifying the gas distributor design. The effect of gas distributor characteristics ( i.e., pore size, free area φ, and relative surface area of the gas distributor to the cross-section of the column R ) on the aeration pattern has been thoroughly discussed. A scale-up ratio ( S ) for the gas distributor has been proposed. Reliability of aeration intensity in terms of superficial air velocity u sg, which has been commonly used as an indicator of prevailing hydrodynamics and shear stress in lab-scale granular bubble columns, has been discussed; it was demonstrated that u sg could not realistically represent the aforementioned conditions in a larger module. Instead, it was suggested that a greater attention should be paid to bubble size and bubble ascending velocity and thus to the subsequent aeration pattern. Gas holdup has been eventually introduced as a crucial and easy-to-measure controlling parameter for the scale-up of granularreactors.